An Adaptive Time Delay Estimator Based on ETDE Algorithm with Noisy Measurements. Issue 4 (1st July 2017) - Xia, Wei; Jiang, Wenying; Zhu, Lingfeng
Abstract : We address the problem of adaptive time delay estimation with noisy measurements. We develop a computationally efficient adaptive time delay estimator based on Explicit time delay estimation (ETDE) algorithm, by applying the unbiased impulse response estimation approach. In this algorithm, a weighted error function is derived, and the time delay is explicitly parameterized in the filter coefficients and iteratively updated directly by utilizing the modified error function. Simulations validate the performance of the proposed algorithm for colored input and low signal‐to‐noise ratio scenarios.